PERUBAHAN LAJU JANTUNG DAN TEKANAN DARAH ARTERI RERATA (MAP) SAAT INDUKSI ANESTESI (Perbandingan antara Propofol 1 mg/kgbb iv dan Ethomidate 0,3 mg/kgbb iv dengan Ko-Induksi Fentanyl 2 μg/kgbb iv) - , BAMBANG SOEKOTJO ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Background: propofol is known as a good and a safe anesthetic induction drug. It has rapid onset, rapid recovery from anesthesia and minimum nausea and vomiting effects. Its advantages are decreasing mean arterial blood pressure (MAP) and cardiac output. The reduction of the dose of the drug by a combination with fentanyl has a stable hemodynamic effect after anesthetic induction because the combination works synergically. Objective: this study was aimed to find out an effective dose of propofol for anesthetic induction that results in lighter change in heart rate and mean arterial blood pressure (MAP) if are compared to their changes from etomidate. Method: the used method was a doble-blind randomized controlled trial (RCT). The subjects were 168 patients and divided in two groups, which were group A (propofol 1 mg/kgbw iv) and group B (etomidate 0.3 mg/kgbw iv). Each of them used anesthetic co-induction of fentanyl 2 µg/kgbw iv. The inclusion criteria were men or women of 18-50 years of age, the physical status of ASA I and II, elective operation procedure under general anesthesia, and BMI >20 and <30 kg/m2. The exclusion criteria were neurosurgery, cardiac surgery and caesarian section, hypovolemic, hypothermia, hyperthyroid, histroyof allerty to fentalyl, propofol and etomidate. Systole and diastole blood pressure, arterial blood pressure, heart rate and saturation were measured before the anesthetic induction and 3 minutes after negative eyelash reflect. The data ware analyzed using independent t-test and chi-square (p<0.05). The results: the decreased of the mean arterial blood pressure in the propofol group was 12.30 ± 5.93 mmHg (13.64%) and the etomidate group was 18.20 ± 6.60 mmHg (19.02%) (p = 0.007). The decrease in the heart rate of the propofol group was 13.17 ± 7.52 x/minute or 14% and etomidate group was 13.66 ± 7.50 x/minute or 14.28% at p = 0.606. Conclusion: Under co-induction with fentanyl 2 µg/kgbw iv, the anesthetic induction with propofol 1 mg/kgbw iv resulted in slighter decrease of mean arterial blood pressure (MAP) than that with etomidate 0.3 mg/kgbw iv (12,30 ± 5,93 mmHg vs. 18,20 ± 6,60 mmHg) (p = 0.007), while the changes in the heart rate were not significant between two groups (13,17 ± 7,52 x/minute vs. 13,66 ± 7,50 x/minute) (p = 0.606).